Effects of Noisy Galvanic Vestibular Stimulation on the Muscle Activity and Joint Movements in Different Standing Postures Conditions - Mitsutake, Tsubasa; Taniguchi, Takanori; Nakazono, Hisato; Yoshizuka, Hisayoshi; Sakamoto, Maiko (Frontiers in Human Neuroscience, 2022)
Objective Noisy galvanic vestibular stimulation (nGVS) is an effective method for stabilizing posture; however, little is known regarding the detailed muscle activity and joint movement in the standing posture. This study aimed to clarify the changes in the lower limb muscle activity and joint angular velocity by nGVS intervention using the simultaneous assessment method of inertial measurement units and surface electromyography (EMG). Methods Seventeen healthy participants were assessed for their physical responses under four conditions (standing on a firm surface with eyes-open/eyes-closed, and a foam surface with eyes-open/eyes-closed) without stimulation (baseline) and with stimulation (sham or nGVS). Noise stimuli were applied for 30 s at a level below the perceptual threshold. The body control response was evaluated using EMG activity and angular velocity of the lower limbs. Result Regarding the change from baseline for each parameter, there was a significant interactive effect of EMG activity in the muscle type × intervention and EMG activity and angular velocity in the condition × intervention. Post hoc analysis revealed that the angular velocity was significantly decreased in the abduction-adduction direction in the standing on a foam surface with eyes-closed condition compared to that with eyes-open in the nGVS intervention. Conclusion Our results suggest that nGVS altered physical responses in different standing postural conditions. The present study is exploratory and therefore the evidence should be investigated in future studies specifically target those muscle activities and joint motion parameters.